UNCOVERING IDEOLOGY THROUGH TRANSITIVITY: A STUDY OF PRESIDENT JOKOWI’S APOLOGY - Megah S., Suswanto Ismadi; Sugiharti, Sri; Kadir, Zulida Abdul; Alsanafi, Ismael Hasan; Kazmi, Saira (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2025)
In contemporary democratic societies, political apologies have evolved into strategic rhetorical acts used by state leaders to manage public perception, repair moral standing, and reinforce political values. In Indonesia, President Joko Widodo’s public apology near the end of his presidency attracted widespread attention and provoked discourse about its underlying ideological motives. Rather than a spontaneous expression of regret, the apology appeared to be a calculated act of political communication, shaped by cultural values and designed to influence the public’s perception of his leadership. This study aims to uncover the ideological tendencies embedded in Jokowi’s apology by analyzing how the apology is represented in two prominent English-language newspapers in Indonesia, The Jakarta Post (TJP) and The Jakarta Globe (TJG). It seeks to determine how transitivity choices in the language are used to convey deeper political and cultural meanings. Employing a qualitative research design supported by quantitative content analysis, the study integrates Fairclough's Critical Discourse Analysis (CDA) and Halliday's Systemic Functional Linguistics (SFL), particularly the transitivity framework, to examine 43 clauses extracted from news articles published in TJP and TJG. The transitivity analysis reveals that material processes dominate the discourse (40.5%), followed by mental (25.5%) and verbal (23.2%) processes. In terms of participant roles, Actor and Sayer occur most frequently, indicating that Jokowi strategically presented himself as an active doer and a sincere speaker. These linguistic patterns suggest a deliberate construction of identity, emphasizing responsibility, empathy, and leadership. The analysis further shows how Jokowi's apology aligns with Javanese cultural ideals of humility and Islamic values of repentance, which are embedded in Indonesian socio-political discourse. The findings contribute to a broader understanding of how political apologies are not only personal but also ideological acts embedded in media discourse. This study highlights the usefulness of integrating CDA and SFL in uncovering how language functions to maintain power, shape public memory, and preserve political legitimacy in post-presidency contexts. It also underscores the cultural specificity of apology strategies in Indonesia, suggesting that future discourse studies consider local traditions and values when analyzing political speech.